Tunisia : 2007 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Tunisia. (IMF Staff Country Reports; Country Report, 2007)
This 2007 Article IV Consultation highlights that effective economic management and an outward-oriented development strategy have contributed to placing Tunisia's economic performance over the past decade among the best in the region. Real GDP growth accelerated from 4 percent in 2005 to 5.4 percent in 2006 owing to a rebound in agricultural output, expansion of nontextile manufacturing, and vitality of the services sector. Tunisia's key challenge is to create enough jobs for the fast-growing university graduate population while reinserting the already large number of unemployed.